2018
DOI: 10.12788/ajo.2018.0051
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Grade III Acromioclavicular Separations in Professional Baseball Pitchers: A Survey of Major League Baseball Team Physicians

Abstract: Despite advancements in surgical technique and understanding of throwing mechanics, controversy persists regarding the treatment of grade III acromioclavicular (AC) joint separations, particularly in throwing athletes. Twenty-eight major league baseball (MLB) orthopedic team physicians were surveyed to determine their definitive management of a grade III AC separation in the dominant arm of a professional baseball pitcher and their experience treating AC joint separations in starting pitchers and position play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…A systematic review examining type III injuries found equivalent clinical outcomes of patients managed operatively and nonoperatively, with a quicker return to work and sport for the nonoperative group [ 48 ]. Surveys have found that most surgeons manage type III injuries nonoperatively in the Netherlands [ 49 ], United Kingdom [ 50 ], and the United States [ 51 , 52 ].…”
Section: Management Of Acromioclavicular Joint Injuriesmentioning
confidence: 99%
“…A systematic review examining type III injuries found equivalent clinical outcomes of patients managed operatively and nonoperatively, with a quicker return to work and sport for the nonoperative group [ 48 ]. Surveys have found that most surgeons manage type III injuries nonoperatively in the Netherlands [ 49 ], United Kingdom [ 50 ], and the United States [ 51 , 52 ].…”
Section: Management Of Acromioclavicular Joint Injuriesmentioning
confidence: 99%
“… ** References 5 7 , 10 , 14 , 15 19 , 21 , 24 , 25 , 27 , 29 , 32 , 33 , 35 , 37 39 , 41 43 , 45 , 49 . …”
unclassified